Phoenix - Stone, Jeff (Stone, Jeff. Five ancestors. Out of the ashes, 2012)
"When their home is robbed, thirteen-year-old Phoenix Collins, an up and coming amateur dirt-bike racer, discovers a shocking mystery about his grandfather, and Phoenix must travel to China and then to Texas to find some answers"--